Sleep, ageing and night work - Pires, M.L.N. [UNESP]; Teixeira, C.W.; Esteves, A.M.; Bittencourt, L.R.A.; Silva, R.S.; Santos, R.F.; Tufik, S.; Mello, M.T. (Associação Brasileira de Divulgação Científica (ABRADIC), 2009)
Studies have shown that the frequency or worsening of sleep disorders tends to increase with age and that the ability to perform circadian adjustments tends to decrease in individuals who work the night shift. This condition can cause consequences such as excessive sleepiness, which are often a factor in accidents that occur at work. The present study investigated the effects of age on the daytime and nighttime sleep patterns using polysomnography (PSG) of long-haul bus drivers working fixed night or day shifts. A total of 124 drivers, free of sleep disorders and grouped according to age (<45 years, N = 85, and ≥45 years, N = 39) and PSG timing (daytime (D) PSG, N = 60; nighttime (N) PSG, N = 64) participated in the study. We observed a significant effect of bedtime (D vs N) and found that the length of daytime sleep was shorter [D: <45 years (336.10 ± 73.75 min) vs N: <45 years (398 ± 78.79 min) and D: ≥45 years (346.57 ± 43.17 min) vs N: ≥45 years (386.44 ± 52.92 min); P ≤ 0.05]. Daytime sleep was less efficient compared to nighttime sleep [D: <45 years (78.86 ± 13.30%) vs N: <45 years (86.45 ± 9.77%) and D: ≥45 years (79.89 ± 9.45%) and N: ≥45 years (83.13 ± 9.13%); P ≤ 0.05]. An effect of age was observed for rapid eye movement sleep [D: <45 years (18.05 ± 6.12%) vs D: ≥45 years (15.48 ± 7.11%) and N: <45 years (23.88 ± 6.75%) vs N: ≥45 years (20.77 ± 5.64%); P ≤ 0.05], which was greater in younger drivers. These findings are inconsistent with the notion that older night workers are more adversely affected than younger night workers by the challenge of attempting to rest during the day.
Keywords: Sleep; Shift work; Night work; Aging; Polysomnography; REM; Slow wave sleep (SWS)